Perbandingan Hasil Penataan Rambut Bergelombang Hollywood Wave Menggunakan Curly Iron Diameter 25 mm dengan Curly Iron Diameter 38 mm pada Tata Rias Foto - Caca Marshanda,; Merita Yanita, (Student Scientific Creativity Journal, 2024)
Hair stylists in using curly iron are still not varied, students still use flat iron rather than curly iron for hair styling. The purpose of this research is to determine the comparison of the results and curl durability of curls using a 25 mm diameter curling iron and a 38 mm diameter curly iron for Hollywood Wave wavy hair styling. This research uses pre-experimental research methods. The sample in this research was 6 Cosmetology and Beauty students class of 2020. Data collection techniques using observation and documentation. The data analysis techniques uses descriptive analysis, prerequisite tests, namely normality tests and homogeneity tests, and hypothesis tests. The results of research from the comparison of Hollywood Wave wavy hair styling showed that the results of the curl shape using 25 mm and 38 mm diameter curly iron were considered quite neat, and from the aspect of curl durability or hair waves were considered resistand using a 25 mm diameter curly iron. And there is a significant difference in Hollywood Wave wavy hair styling using a 25 mm diameter curly iron with a 38 mm diameter which is proven by the significance value obtained of 0,000. This research can be used as education abaout the use of curling tools with different diameters, and it is recommended to use a 25 mm diameter curly iron for styling Hollywood Wave hair because the waves are more “S” shaped.